Efeito da tepoxalina sobre as funções renal e hepática em gatos submetidos à hipotensão com isofluorano - Freitas, Gabrielle Coelho (2012)
The aim of this study was to evaluate acute and subacute renal and hepatic toxicity of the oral administration of tepoxalin in cats submitted to hypotension with isoflurane. Eighteen adult male mongrel cats were used in this study, weighing between 3 and 5 kg and clinically healthy. The animals were divided into three groups, which were anesthetized and submitted to hypotension with isoflurane (CON), or which, in addition, tepoxalin was administered two hours prior to the hypotension procedure (PRE) or after the hypotension procedure (POS). The animals from groups PRE and POS also received the same doses of tepoxalin every 24 hours, during the five days following the procedure. In order to achieve a condition of moderate hypotension, animals were induced and maintained with isoflurane in variable concentration, for maintenance of mean arterial pressure (MAP) between 45 and 60 mmHg, during 60 minutes. Complete blood count and serum concentrations of alanine aminotransferase (ALT), alkaline phosphatase (FA) and urea (U) were evaluated at baseline and 24 hours, 48 hours and 7 days after hypotension. Serum concentration of creatinine (Cr), fractional excretion of sodium (FENa) and urinary concentrations of Cr, gamma-glutamyl transferase (GGT), proteinuria and albuminuria were evaluated at baseline and 24 hours, 48 hours and 7 days after hypotension. The model chosen was efficient in maintaining the proposed condition of hypotension. No physiological changes were observed in complete blood count, serum biochemistry profile (ALT, FA, U and Cr), FENa and urinary GGT. An increase in urine protein-creatinine ratio was observed in CON and PRE at 24 and 48 hours after hypotension. Urine albumin-creatinine ratio showed increase in CON at 24 hours and maintained elevated values with regard to the other groups until 7 days after hypotension. The authors conclude that administration of tepoxalin does not cause changes in hepatic parameters, urea, creatinine, fractional excretion of sodium and urinary GGT in cats submitted to anesthetic hypotension. However, there is a risk of mild renal injury by administering the drug prior to the hypotensive procedure.